Rare cutaneous verrucous carcinoma in the femoral region: a case report - Restu Nur Rohmah; Muhammad Yamsun; Sri Hidayah Nurlela Syafiie (Universa Medicina, 2023)
BackgroundVerrucous carcinoma (VC) is a well-differentiated variant of squamous cell carcinoma (SCC) characterized by slow growth and low metastatic potential. Cutaneous verrucous carcinoma (CVC) or papillomatosis cutis carcinoides is the term used for VC in other locations than the oral, anogenital, and plantar regions. This rare tumor has a contradictory “benign” histology, but markedly aggressive clinical behavior. We present this case as background knowledge to corroborate clinical course, diagnosis, histopathology, and treatment options for this infrequent disease. Case DescriptionWe report a verrucous carcinoma on a 79-year-old man’s left thigh. Clinical examination showed a fungating mass with cauliflower-like appearance measuring 5x3x1 cm. Excisional biopsy revealed exo-endophytic proliferation of well-differentiated squamous epithelium invading the dermis with marked hyperkeratosis, parakeratosis, acanthosis, papillomatosis, pushing margins, and minimal cellular atypia (T2N0M0). It was successfully treated by wide local excision, inguinal lymph node dissection, and adjuvant radiotherapy. Follow-up after 1 year showed good wound healing without any loss of function or recurrence. ConclusionCutaneous verrucous carcinoma is a subtype of a low-grade SCC and is not an SCC with a verrucous presentation. Identification of the clinicopathological features is essential to distinguish CVC from its mimics and to make an early diagnosis. Although slow growth and confusing early-stage appearances can lead to delay in diagnosis or to misdiagnosis, this case has not raised many diagnosis problems regarding the cardinal manifestations of CVC. Regardless of any available therapeutic methods, surgical excision with safety margins is still a priority and CVC requires aggressive treatment.